Intraoral scanner-based monitoring of tooth wear in young adults: 36-month results - Schlenz, Maximiliane Amelie; Schlenz, Moritz Benedikt; Wöstmann, Bernd; Glatt, Anna Sophia; Ganss, Carolina; Justus Liebig University Giessen (My University, 2024)
Objectives: The study continues our longitudinal observation of wear aiming to further monitoring of progression and lesion morphology and to identify relationships with assumed aetiological factors. Materials and methods: Molars (FDI #36 or #46) of 74 participants (23.8 ± 2.2 years) were scanned (Trios 3, 3Shape) at the third follow-up (T3; observation period 1,111 ± 10 days). Data sets from T3, T2 (24-month follow-up) and T1 (12-month follow-up) were superimposed with baseline in a 3D analysis software (GOM Inspect). Wear was quantified as maximum vertical tissue loss (µm; median, 95% CI) in various occlusal areas (4/5 cusps and 2 ridges). Morphologies were classified into cupping (C), facet (F), and combined cupping-facet (CF). Aetiological factors were assessed with questionnaires. Results: Wear increased at T3 significantly at low rates in all areas of the occlusal surface (median between 7.0 (4.0;10.5) and 9.5 (6.0;15.0) µm). There was a clear trend for higher loss values in males, but no association with other factors such as nutrition. C and CF showed significantly higher loss values than F. Areas without initial wear developed F first, which either persisted or developed into C and CF. Conclusions: Wear continued at low rates with C/CF morphology and sex as significant factors. Cupped lesions seem to develop from facets and thus may not be a valid diagnostic criterion for erosive tooth wear. Clinical relevance: Wear is a cumulative process that apparently follows complex mechanisms that cannot be conceptualized in simplified terms; C and CF may be indicators for higher progression rates.
Keywords: ddc:610